Differential expression and regulation of vitamin D hydroxylases and inflammatory genes in prostate stroma and epithelium by 1, 25-dihydroxyvitamin D in men with prostate cancer and an in vitro model. Issue 148 (April 2015) - Giangreco, Angeline A.; Dambal, Shweta; Wagner, Dennis; Van der Kwast, Theodorus; Vieth, Reinhold; Prins, Gail S.; Nonn, Larisa
Abstract: Previous work on vitamin D in the prostate has focused on the prostatic epithelium, from which prostate cancer arises. Prostatic epithelial cells are surrounded by stroma, which has well-established regulatory control over epithelial proliferation, differentiation, and the inflammatory response. Here we examined the regulation of vitamin D-related genes and inflammatory genes by 1α, 25-dihydroxyvitamin D3 (1, 25(OH)2 D) in laser-capture microdissected prostate tissue from a vitamin D3 clinical trial and in an in vitro model that facilitates stromal–epithelial crosstalk . Analysis of the trial tissues showed that VDR was present in both cell types, whereas expression of the hydroxylases was the highest in the epithelium. Examination of gene expression by prostatic (1, 25(OH)2 D) concentrations showed that VDR was significantly lower in prostate tissues with the highest concentration of 1, 25(OH)2 D, and down-regulation of VDR by 1, 25(OH)2 D was confirmed in the primary cell cultures. Analysis of inflammatory genes in the patient tissues revealed that IL-6 expression was the highest in the prostate stroma while PTGS2 (COX2) levels were lowest in the prostate cancer tissues from men in the highest tertile of prostatic 1, 25(OH)2 D. In vitro, TNF-α, IL-6 and IL-8 were suppressed by 1, 25 (OH)2 D in the primary epithelial cells, whereas TNF-α and PTGS2 were suppressed by 1, 25(OH)2 D in the stromal cells. Importantly, the ability of 1, 25(OH)2 D to alter pro-inflammatory-induced changes in epithelial cell growth were dependent on the presence of the stromal cells. In summary, whereas both stromal and epithelial cells of the prostate express VDR and can presumably respond to 1, 25(OH)2 D, the prostatic epithelium appears to be the main producer of 1, 25(OH)2 D. Further, while the prostate epithelium was more responsive to the anti-inflammatory activity of 1, 25 (OH)2 D than stromal cells, stroma–epithelial crosstalk enhanced the phenotypic effects of 1, 25(OH)2 D and the inflammatory process in the prostate gland.